The challenges of AI in administrative law and the need for specific legal remedies - Jakubek-Lalik, Jowanka (Central European Public Administration Review, 2024)
There are many new challenges to the classic approach to decision-making in administrative law. Public authorities are discovering the potential of AI systems to improve the efficiency and accuracy of administrative proceedings. However, automated decision-making (ADM) and AI-supported decision-making create new dilemmas, especially in relation to accountability, data protection, and general principles of administrative law. The benefits of AI should therefore be assessed together with the associated risks and threats, with adequate means for control and supervision. The use of AI tools is growing also in the Polish public administration, as is interest in simplifying administrative proceedings and automating the issuance of administrative decisions. However, these trends should be carefully monitored, especially from the perspective of citizens’ rights and potential errors that may differ from the classical, non-automated administrative proceedings. Purpose: This article examines the challenges of introducing AI tools into administrative law and proceedings, as well as the need for specific legal remedies. It questions whether the remedies are the same as in traditional administrative proceedings and whether the instruments provided in existing legislation suffice to ensure adequate protection of citizens’ rights? The methodology used includes an analysis of the legislation and policies, desk research on practical examples, and insights from discussion at the EGPA 2024 Conference. The findings focus on the analysis of existing legislation both in terms of its applicability and practical implementation, especially in light of AI use in public administration. The most important aspect is the link between the use of AI tools and the potential need to design new or adapt existing legal remedies in both imperious and non-imperious domains of public administration, with a special focus on ADM challenges. Practical implications address the new challenges AI poses to decision-making in administrative law. Through practical examples, it also discusses to what extent legal remedies should be tailored to AI tools and how human rights might be affected, necessitating protective measures. These implications are important not only from a legal standpoint, but also for legal practitioners and the public administration as a whole. Originality and value of the article lie in the discussion on the challenges of administrative proceedings and legal remedies in the era of AI. This topic is both highly relevant and timely, as the use of AI will undoubtedly shape the future of public administration proceedings and other activities.
Keywords: ADM; administrative law; administrative proceedings; AI; automated decision making; avtomatizirano odločanje; Polish public administration; poljska javna uprava; umetna inteligenca; upravni postopki; upravno pravo